Empowering 21st Century Educators: Harnessing Learning Management Skills for Personalised Learning - Adeoye, Moses Adeleke; Azisi, Azisi; Adebiyi, Sunday Adetunji; Sabela, Windari (Pedagogik: Jurnal Pendidikan, 2025)
The rapid advancement of technology has transformed educational environments, making Learning Management Systems (LMS) a pivotal tool for facilitating personalised learning experiences. This research explores LMS’s effectiveness in enhancing student engagement and academic performance while identifying essential skills educators need to harness these technologies effectively. A systematic literature review was conducted, analysing existing studies on LMS, personalised learning, and educator competencies. The findings reveal that LMS significantly improve customised learning through adaptive learning pathways, gamification and increased accessibility. Educators with digital literacy, data-driven decision-making and collaborative learning strategies are better positioned to create engaging learning environments and improve student outcomes. However, technological barriers and the need for ongoing professional development persist. The study concludes that while LMS hold great promise, addressing these challenges is crucial for maximising their potential. This research contributes to the field by providing a comprehensive understanding of how LMS can be effectively utilised in educational settings, highlighting the importance of equipping educators with the necessary skills. The insights gained from this study can inform academic institutions and policymakers in designing and implementing training programs, ensuring that educators and learners can thrive in increasingly digital learning environments. Ultimately, this research emphasises the vital role of LMS in shaping the future of education and the need for continuous adaptation and improvement in teaching practices.